Immunities of diplomatic means of communication and liability for misuse - Aloush, Hind Abdul Amir (Arab Journal for Sciences and Research Publishing, 2017)
The importance of this research is that it concerns the various diplomatic connections (classical and modern) also include the immunities and privileges that diplomatic missions have in regard to the mechanisms of their transmissions, travels, bags, and documents. Whereas, the concern of this study is to give answers of questions regarding the extent of rights that the diplomatic missions have through using modern and diplomatic mechanisms such as (Internet and satellites) that because Vienna convention has not answered this question, also those mechanisms were not using at the time of preparing Vienna convention for diplomatic relations on 1961. At the same time, the receiver states for a mission who violate their commitments under articles (22 and 29) in Vienna convention 1961, they will be inquired and liable for all damages to the state that sent the mission. This is applicable to the mission itself too where it abuses one of the connection mechanisms and makes a damage whether it is a material or ethical damage or whether the damage is direct or indirect. Those all require an absolute agreement in international actions.